A Functional Land Management conceptual framework under soil drainage and land use scenarios. Issue 56 (February 2016) - Coyle, Cait; Creamer, Rachel E.; Schulte, Rogier P.O.; O'Sullivan, Lilian; Jordan, Phil
Highlights: We develop a conceptual framework on Functional Land Management to inform and support policies on sustainable intensification in agriculture. Conceptual diagrams are used to illustrate the individual supply of five key soil ecosystem services (soil functions) in the agronomic sector. A functional soil matrix shows the variation in the multi-functional capacity of the soil under different types of land use and soil drainage. A case study is provided to demonstrate the application of multi-functional land use planning at national level. Abstract: Agricultural soils offer multiple soil functions, which contribute to a range of ecosystem services, and the demand for the primary production function is expected to increase with a growing world population. Other key functions on agricultural land have been identified as water purification, carbon sequestration, habitat biodiversity and nutrient cycling, which all need to be considered for sustainable intensification. All soils perform all functions simultaneously, but the variation in the capacity of soils to supply these functions is reviewed in terms of defined land use types (arable, bio-energy, broadleaf forest, coniferous forest, managed grassland, other grassland and Natura 2000) and extended to include the influence of soil drainage characteristics (well, moderately/imperfect, poor and peat). This latter consideration is particularly important in the European Atlantic pedo-climatic zone; the spatial scale of this review. This review develops a conceptual framework on the multi-functional capacity of soils, termed Functional Land Management, to facilitate the effective design and assessment of agri-environmental policies. A final functional soil matrix is presented as an approach to show the consequential changes to the capacity of the five soil functions associated with land use change on soils with contrasting drainage characteristics. Where policy prioritises the enhancement of particular functions, the matrix indicates the potential trade-offs for individual functions or the overall impact on the multi-functional capacity of soil. The conceptual framework is also applied by land use area in a case study, using the Republic of Ireland as an example, to show how the principle of multi-functional land use planning can be readily implemented.